Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/jacs.1c01709
|View full text |Cite
|
Sign up to set email alerts
|

Direct Dynamics Trajectories Reveal Nonstatistical Coordination Intermediates and Demonstrate that σ and π-Coordination Are Not Required for Rhenium(I)-Mediated Ethylene C–H Activation

Abstract: The C−H activation reaction between Cp(PMe 3 ) 2 Re and ethylene results in kinetic selectivity for the Re-vinyl hydride I over the thermodynamically more stable Cp(PMe 3 ) 2 Re(η 2 -ethylene) πcomplex II. While transition-state and variational transition-state structures were located for individual pathways leading to I and II, DFT and CCSD(T) energies predict a large kinetic selectivity of 10 2 − 10 4 , which is incompatible with the experimental 10:1 ratio. DFT direct quasiclassical trajectories revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…For example, in the C–H activation between methane and [Cp*­(PMe 3 )­Ir III (CH 3 )] + , as well as the β-hydrogen transfer for [Cp*Rh III (Et)­(ethylene)] + , despite a fully characterized intermediate on each of the DFT potential energy landscapes direct dynamics simulations revealed that the intermediate is either sometimes or always skipped due to dynamical coupling of multiple reaction steps through dynamic matching or the lack of IVR. We also discovered dynamic effects, specifically dynamical pathway branching, in the reaction between Tp­(NO)­(PR 3 )W and benzene as well as Cp­(PMe 3 ) 2 Re and ethylene . Related organometallic dynamic effects were reported for hydrogenation reaction steps of (Cl)­(CO)­(PH 3 )­Ru II (H)­(H 2 )­(C 2 H 4 ), Rh-carbenoid C–H bond insertion, and Au/Ag arene C–H functionalization .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, in the C–H activation between methane and [Cp*­(PMe 3 )­Ir III (CH 3 )] + , as well as the β-hydrogen transfer for [Cp*Rh III (Et)­(ethylene)] + , despite a fully characterized intermediate on each of the DFT potential energy landscapes direct dynamics simulations revealed that the intermediate is either sometimes or always skipped due to dynamical coupling of multiple reaction steps through dynamic matching or the lack of IVR. We also discovered dynamic effects, specifically dynamical pathway branching, in the reaction between Tp­(NO)­(PR 3 )W and benzene as well as Cp­(PMe 3 ) 2 Re and ethylene . Related organometallic dynamic effects were reported for hydrogenation reaction steps of (Cl)­(CO)­(PH 3 )­Ru II (H)­(H 2 )­(C 2 H 4 ), Rh-carbenoid C–H bond insertion, and Au/Ag arene C–H functionalization .…”
Section: Resultsmentioning
confidence: 74%
“…We also discovered dynamic effects, specifically dynamical pathway branching, in the reaction between Tp(NO)(PR 3 )W and benzene 40 as well as Cp(PMe 3 ) 2 Re and ethylene. 41 Related organometallic dynamic effects were reported for hydrogenation reaction steps of (Cl 42 Rh-carbenoid C−H bond insertion, 43 and Au/Ag arene C−H functionalization. 44 There are also recent reports of dynamic effects for Ru geminal hydroboration, 45 Fe Diels− Alder reactions, 46 Fe arene amination, 47 and Pd transmetalation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 11 shows a potential-energy landscape and the structures located with static DFT calculations. 2 From an ethylene σ-coordination structure, there is branching with two pathways, one pathway leading to the Re vinyl hydride and the other leading to the Re(η 2 -ethylene) π-complex. While these two pathways possibly explain the reaction selectivity, CCSD(T) calculations showed that a transition-state theory approach did not match the experimental selectivity.…”
Section: Making Non-irc Connectionsmentioning
confidence: 99%
“…Quasiclassical direct dynamics trajectories provided a more reasonable selectivity model and revealed dynamically connected reaction pathways. 2 For this reaction, trajectories were initiated at both transition-state structures as well as structures identified using metadynamics simulations. Trajectories resulted in direct formation of either the Re vinyl hydride I or to the πcomplex II.…”
Section: Making Non-irc Connectionsmentioning
confidence: 99%
“…The reactivity of energetically non-equilibrated intermediates (kinetically activated, "hot" intermediates) has received significant attention recently. 24,26 It has been shown that dynamic effects and the amount of excess energy and how it is distributed can control the reactivity of intermediates in solution, 27,28 in organometallic reactions 29,30 and in enzymes. [31][32][33] Here we show that the high chemoselectivity in metal-oxo mediated alkene oxidation by iron porphyrin-type catalysts is a consequence of the radical's dynamic behavior in its kinetically (vibrational) activated state.…”
Section: Introductionmentioning
confidence: 99%